The Role of Financial Literacy in Investment Selection in the Millennial Generation in Cikampek District - Jumhari, Achmad; Mohammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
In today’s economic context, many individuals are looking for additional sources of income outside of their primary job. One strategy that many choose is investing. This study aims to determine the role of financial literacy in investment selection. This research used a quantitative descriptive approach conducted in Cikampek District, Karawang Regency. The respondents who are in focus are the Millennial Generation aged 24-43 years. The total population is 40,219 based on demographic data from Cikampek District in 2023. The sample was determined using the Slovin formula with 100 people, with an inaccuracy tolerance of 10 percent. Samples are taken using the non-probability sampling method by applying a purposive sampling approach to determine the sample. Data collection involves the use of primary data and secondary data. Data was collected through questionnaires using the Likert scale. The data was analyzed using multivariate structural equation modelling (SEM) analysis, with the analysis tool being SmartPLS 4. The dimensions to be used in this study for financial literacy variables include financial understanding, savings and lending, financial planning and management, and risk and benefit aspects. Meanwhile, investment selection variables include rate of return, investment risk, investment security, liquidity, time value of money, real wealth investment, personal wealth investment, financial investment, commodity investment, and investment options in the short, medium, and long term. This study’s results prove that financial literacy has a positive and significant influence on investment selection.